Rebound increase in seizure susceptibility but not isolation-induced calls after single administration of clonazepam and Ro 19-8022 in infant rats - Mikulecká, A; Mareš, P; Kubová, H (Epilepsy & behavior, 2011)
The purpose of our study was to determine whether a single administration of anticonvulsant doses of two ligands of benzodiazepine receptors, clonazepam and Ro 19-8022, leads to development of rebound phenomena in immature 12-day-old rats. Three tests were used: pentylenetetrazole (PTZ)-induced seizures, isolation-induced ultrasonic vocalizations, and motor performance. Susceptibility to the convulsant effects of PTZ decreased 24 hours, but increased 48 hours, after clonazepam administration. Ultrasonic vocalizations were completely suppressed 30 minutes and 3 hours after clonazepam; a moderate inhibitory effect persisted even at 48 hours. Motor abilities were slightly compromised up to 3 hours. Similar effects of Ro 19-8022 on PTZ-induced seizures and ultrasonic vocalizations were observed 24 and 48 hours after administration; motor performance was not affected. Rebound proconvulsant effects followed different time courses after administration of the two benzodiazepine receptor ligands in developing animals. Anxiolytic-like effects of these drugs were still present at the time when animals exhibited rebound proconvulsant effects.
Keywords: Pentylenetetrazole; Seizures; pohybová aktivita; Pyrrolidines; GABA Modulators; vokalizace zvířat; analýza rozptylu; novorozená zvířata; záchvaty; Analysis of Variance; krysa rodu Rattus; zvířata; pentylentetrazol; Clonazepam; potkani Wistar; Disease Susceptibility; náchylnost k nemoci; Quinolizines; Animals, Newborn; chinoliziny; Rats, Wistar; Male; receptory GABA-A; Rats; GABA modulátory; klonazepam; Motor Activity; Animals; mužské pohlaví; pyrrolidiny; Receptors, GABA-A; Vocalization, Animal